A New Sesquiterpene from Nicotiana tabacum and Its Cytotoxicity - Chen, Yong-Kuan; Meng1, Chunyang; Zhongbi, Su; Wang, Lu; Yang, Guangyu-Yu; Miao, Ming-Ming (Asian Journal of Chemistry, 2014)
A new sesquiterpene, tabsesquiterpene A (1) was isolated from the leaves of Nicotiana tabacum. Its structure was elucidated by spectroscopic methods, including extensive 1D and 2D NMR techniques. Compound 1 was tested for its cytotoxicity. The results showed that 1 exhibited modest cytotoxicity against SHSY5Y, PC3 and MCF7 with IC50 values of 6.9, 4.5 and 8.8 μM, respectively.